Understanding business cycles: credit supply, household debt and financial crises in Portugal - Santos, Ricardo Filipe Pereira (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management